Physicochemical characterization of soil occupied by carob tree (Ceratonia siliqua L.) in Morocco - Ismail E ttaleb; Jalila Aoujdad (Journal of Global Innovations in Agricultural Sciences)
Carob tree cultivation requires a good understanding of soil nutrient availability. Therefore, several farmers and other stakeholders have little scientific knowledge in soil standards for carob cultivation. This study aims to characterize and assess the physicochemical quality of carob soils to improve crop production. Data collection involved soil sampling at 0-20 and 20-40 cm depth beneath carob trees in 19 different regions of Morocco for 2019 year. Obtained results on the physicochemical analyses of the soil (texture, pH (H2O), electrical conductivity (EC), total limestone, organic matter (OM), organic carbon (OC), total nitrogen (TN), C/N ratio, assimilable phosphorus (P)) indicated that soils from various studied stations exhibited sandy loam texture, with neutral to slightly alkaline pH values (ranging from 6.39 to 7.62). Regarding other elements, the soils of all studied stations have a content of organic carbon not exceeding 5.11%, an organic matter ranging from 0.62 to 8.70% and a content of total nitrogen below 1.82%, while C/N ratio in soils is relatively higher. However, in all the stations, soil is considered low in available phosphorus. Total limestone contents are higher in different stations. Furthermore, soil electrical conductivity ranges from low value (0.15 mS/cm) to moderate value (2.34 mS/cm). For the most variables, small differences in soil physicochemistry are found between different stations. These findings may elucidate the carob trees’ adaptability to various soil types. Keywords: Carob tree, Ceratonia siliqua L., soil characterization, soil texture, nutrient availability, pH, electrical conductivity, Morocco.